OP0058 Efficacy of Sildenafil on Ischaemic Digital Ulcer Healing in Systemic Sclerosis: The Placebo-Controlled Seduce Study. (9th June 2015) - Hachulla, E.; Hatron, P.-Y.; Carpentier, P.; Agard, C.; Chatelus, E.; Jego, P.; Mouthon, L.; Queyrel, V.; Fauchais, A.-L.; Michon-Pasturel, U.; Jaussaud, R.; Mathian, A.; et al.
Abstract : Background: Previous data suggested an effect of sildenafil on digital ulcer (DU) healing in Scleroderma (SSc) patients, which needed to be validated in a large randomized controlled study. Objectives: To assess the effect of sildenafil, a PDE-5 inhibitor, on DU healing in SSc. Methods: Randomised, placebo-controlled study in SSc patients to assess the effect of sildenafil 20 mg or placebo, 3 times daily for 12 weeks on ischaemic DU healing. The primary endpoint was the time to healing for each DU. Time to healing was compared between groups using Cox models for clustered data (two-sided tests, p=0.05). Results: Intention-to-treat (ITT) analysis involved 83 patients with a total of 192 DUs (89 in the sildenafil group and 103 in the placebo group). The hazard ratio (HR) for DU healing was 1.33 [0.88 to 2.00] (p=0.18) and 1.27 [0.85 to 1.89] (p=0.25) when adjusted for the number of DUs at entry, in favour of sildenafil. In the per protocol (PP) population, the HRs were 1.49 [0.98 to 2.28] (p=0.06) and 1.43 [0.93 to 2.19] p=0.10. The mean number of DUs per patient was lower in the sildenafil group compared to the placebo group at week (W) 8 (1.23±1.61 versus 1.79±2.40 p=0.04) and W12 (0.86±1.62 versus 1.51±2.68, p=0.01) resulting from a greater healing rate (p=0.01 at W8 and p=0.03 at W12). Conclusions: The primary endpoint was not reached in ITT, partly because of an unexpectedly high healing rate in the placebo group. We found a significant decrease in the number of DUs in favour of sildenafil compared to placebo at W8 and W12, confirming a sildenafil benefit. Acknowledgements: We gratefully acknowledge the Groupe Francophone de Recherche sur la Sclérodermie (GFRS), and the French Scleroderma Patients' Association (Association des Sclérodermiques de France [(ASF]) which helped to distribute the study protocol to its members. This study was supported by an unrestricted research grant from PFIZER. The sponsor had no role in the design of the study, the collection and analysis of the data, or in the preparation of the manuscript. Disclosure of Interest: E. Hachulla Grant/research support from: PFIZER, P.-Y. HATRON: None declared, P. CARPENTIER: None declared, C. AGARD: None declared, E. CHATELUS: None declared, P. JEGO: None declared, L. MOUTHON: None declared, V. QUEYREL: None declared, A.-L. FAUCHAIS: None declared, U. MICHON-PASTUREL: None declared, R. JAUSSAUD: None declared, A. MATHIAN: None declared, B. GRANEL: None declared, E. DIOT: None declared, D. FARGE-BANCEL: None declared, A. MEKINIAN: None declared, J. AVOUAC: None declared, H. DESMUR-CLAVEL: None declared, P. CLERSON: None declared